Influence of C₆H₄(OH)₂ isomers on water disinfection by photocatalysis: a computational study - Elmenaouar, K.; Benbrik, R.; Aamouche, A. (Condensed Matter Physics, 2017)
Solar disinfection by photocatalysis is one of the promising methods used for drinking water disinfection. It leads to the destruction of bacteria like Escherichia Coli (E. Coli). In this paper, we compare our theoretical results with experimental ones done previously by A.G. Rincón and his colleagues concerning the order of decay of C₆H₄(OH)₂ isomers in the presence of titanium dioxide TiO₂, and show the influence of optical properties of those molecules on E. Coli inactivation. According to the adsorption energy parameter, we find that catechol has the highest adsorption degree on titanium dioxide, followed by resorcinol, and finally hydroquinone. Three dihydroxybenzene isomers absorb photons belonging to ultraviolet (UV) range. The lowest absorption energies of resorcinol, catechol and hydroquinone are respectively 3.42, 4.44 and 4.49 eV